2015
DOI: 10.1074/jbc.m115.672626
|View full text |Cite
|
Sign up to set email alerts
|

ATM-dependent Phosphorylation of the Fanconi Anemia Protein PALB2 Promotes the DNA Damage Response

Abstract: Background:The ATM kinase orchestrates DNA damage responses by protein phosphorylation. Results: PALB2 becomes phosphorylated in an ATM-dependent manner. Conclusion: PALB2 phosphorylation is important for cell responses to ionizing radiation-induced DNA damage. Significance: The ATM-PALB2 axis promotes cellular responses to DNA damage.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
17
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 19 publications
(21 citation statements)
references
References 41 publications
4
17
0
Order By: Relevance
“…Consistent with previous reports (23,24), siRNA-mediated depletion of BRCC36 led to increased rates of HR repair (Fig. 1B), whereas inactivation of the HR repair factor PALB2 led to a marked reduction in DSB repair events (26). To directly examine how the BRCC36 DUB contributes to DSB repair, we generated cells that stably express siRNA-resistant versions of BRCC36 WT or its DUB enzymatic mutant BRCC36 H122Q/H124Q (QSQ).…”
Section: Resultssupporting
confidence: 83%
“…Consistent with previous reports (23,24), siRNA-mediated depletion of BRCC36 led to increased rates of HR repair (Fig. 1B), whereas inactivation of the HR repair factor PALB2 led to a marked reduction in DSB repair events (26). To directly examine how the BRCC36 DUB contributes to DSB repair, we generated cells that stably express siRNA-resistant versions of BRCC36 WT or its DUB enzymatic mutant BRCC36 H122Q/H124Q (QSQ).…”
Section: Resultssupporting
confidence: 83%
“…We identified a total of 12 phosphorylation sites on PALB2 (Fig. 3A), a subset of which was shown previously (Ahlskog et al, 2016; Guo et al, 2015; Matsuoka et al, 2007). The N-terminal coiled-coil domain of PALB2 interacts with BRCA1 directly (Fig.…”
Section: Resultssupporting
confidence: 69%
“…ATR may have additional roles in PALB2 regulation. A recent study suggested that the phosphorylation of PALB2 at S157 and S376, two putative ATM/ATR sites, is dispensable for HR but required for the recovery from the DNA damage response (Guo et al, 2015). Another study proposed that the phosphorylation of PALB2 by ATM/ATR at S59, S157, and S376 promotes HR by enhancing the interaction between PALB2 and RAD51 (Ahlskog et al, 2016).…”
Section: Discussionmentioning
confidence: 99%
“…U2OS cells were infected with lentiviral particles carrying RNF169-SFB expression constructs and were subsequently selected by 2 mg/ mL G418. Expression of RNF169-SFB was induced by supplementing cell culture media with doxycycline at 1 ÎŒg/mL for 12 h. Generation of cell lines with constitutive expression of RNF169 (wild type and mutants) and USP7 (wild type and mutants) was performed as previously described (50).…”
Section: Methodsmentioning
confidence: 99%
“…Procedures for indirect immunofluorescence experiments were as previously described (50). Briefly, cells grown as monolayers on coverslips were exposed to ionizing radiation (10 Gy).…”
Section: Methodsmentioning
confidence: 99%